Perioperative Efficiency vs. Quality of Care – Do We Always Have to Choose?. Issue 3 (15th March 2020) - Chernov, Mikhail; Vick, Angela; Ramachandran, Sujatha; Reddy, Shamantha; Leyvi, Galina; Delphin, Ellise
Abstract: Introduction: ATTEMPTS to enforce optimization practices for operating room (OR) efficiency are often interpreted as a "pressure for production" which threatens patient safety. The aim of this study is to assess if and how improvements in OR efficiency affect patient safety and thus the quality of care. Methods: In an attempt to optimize OR efficiency, a new OR management approach "Integrated Practice Improvement Solutions" (IPIS) was developed at the Weiler Division of Montefiore Medical Center in 2011. IPIS is a flexible managerial system based on elements of multiple practice improvement methodologies incorporated into an open source framework. It was implemented in 2012. The data presented covers the period from 2012 through 2014 when the system was temporarily discontinued due to administrative restructuring. Data from 2011 was used as a baseline. The impact of IPIS on patient safety and quality of care was assessed based on quality improvement and patient safety (QIPS) Committee reports covering the same period of time. Results: IPIS implementation resulted in an increase in surgical workload by an average of 10.7%, an increase in OR and anesthesia revenues by 18.5% and 6.9%, respectively, and decreases in turnover time by 15% and overtime for the anesthesia staff by 26%. Based on QIPS reports, the total number of complications potentially attributable to "production pressure" was 0.25%, 0.2% and 0.16% in 2012, 2013 and 2014, respectively compared to 0.21% in 2011 ( p  = 0.56). Conclusions : Gradual implementation of a methodologically structured improvement in OR efficiency has no negative impact on patient safety and quality of care.